Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examinations June 1993: Typewriting - Caribbean Examinations Council (CXC, 1993)
This report contains general and detailed comments on the performance of candidates in the June 1993 Caribbean Secondary Education Certificate Examinations (CSEC) in Typewriting.
Keywords: CXC CSEC examinations